2022
DOI: 10.1021/acsami.1c23342
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polyphenol Liposomes Overcome Gastric Mucus to Treat Helicobacter Pylori Infection and Enhance the Intestinal Microenvironment

Abstract: Infection with Helicobacter pylori (Hp) is one of the leading causes of stomach cancer. The ability to treat Hp infection is hampered by a lack of stomach gastric acid environment. This work introduces a nanoliposome that can rapidly adjust the gastric acid environment to ensure a drug's optimal efficacy. We introduce CaCO 3 @Fe−TP@EggPC nanoliposomes (CTE NLs) that are composed of Fe 3+ and tea polyphenols (TPs) forming complexes on the surface of internal CaCO 3 and then with lecithin producing a phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…A tea polyphenol liposome was designed to treat helicobacter pylori infection, which is one of the main causes of gastric cancer [ 143 ]. The phospholipid layer in this nanoliposome can inhibit the growth of helicobacter pylori via fusion with the bacterial membrane [ 144 ]. Moreover, tea polyphenols in this nanosystem can reduce inflammation and improve the gut microbes to construct a healthier gastrointestinal environment [ 144 ].…”
Section: Progress In Nanocarrier-mediated Delivery Of Polyphenolic Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…A tea polyphenol liposome was designed to treat helicobacter pylori infection, which is one of the main causes of gastric cancer [ 143 ]. The phospholipid layer in this nanoliposome can inhibit the growth of helicobacter pylori via fusion with the bacterial membrane [ 144 ]. Moreover, tea polyphenols in this nanosystem can reduce inflammation and improve the gut microbes to construct a healthier gastrointestinal environment [ 144 ].…”
Section: Progress In Nanocarrier-mediated Delivery Of Polyphenolic Co...mentioning
confidence: 99%
“…The phospholipid layer in this nanoliposome can inhibit the growth of helicobacter pylori via fusion with the bacterial membrane [ 144 ]. Moreover, tea polyphenols in this nanosystem can reduce inflammation and improve the gut microbes to construct a healthier gastrointestinal environment [ 144 ]. This tea polyphenol-based nanoliposome provides a new strategy for treating helicobacter pylori infection and preventing the subsequent development of gastric cancer [ 144 ].…”
Section: Progress In Nanocarrier-mediated Delivery Of Polyphenolic Co...mentioning
confidence: 99%
“…More attention should be paid to how to deliver higher concentrations of polyphenols to target organs to improve their absorption and utilization. The existing polyphenol nano-drug delivery technology may have great potential in this regard [ 121 ]. In fact, studies have demonstrated that polyphenols can provide a powerful environment for tumor immunotherapy by regulating the tumor immune microenvironment (TME) [ 122 ].…”
Section: Summary and Challengementioning
confidence: 99%
“…Similarly, Epigallocatechin gallate (EGCG, tea polyphenol), which is present in green tea, also showed anti-biofilm and anti-infection activities by Stenotrophomonas maltophilia and P. aeruginosa by reduction of C4-AHL production ( Vidigal et al, 2014 ; Hao et al, 2021 ). In mice, these compounds protect mice from infections by different pathogens, including methicillin-resistant S. aureus ( Long et al, 2019 ), H. pylori ( Muhammad et al, 2015 ; Deng et al, 2022 ), and S. typhimurium ( Wang et al, 2021 ; Zhao et al, 2021 ).…”
Section: Quorum Sensingmentioning
confidence: 99%